Exploring the properties of Deer Antler Velvet (DAV) and its potential use in dentistry: a narrative review - Azami, Azalea Nur-Qistina; Mokhtar@Makhtar, Khairani Idah; Mustafa Al-Ahmad, Basma Ezzat; Mohd Kenali, Norzaiti; Sha'ban, Munirah; Ahmad, Azlina (Faculty of Dentistry, University of Malaya, 2024)
For centuries, deer antler velvet (DAV) has been a staple in traditional medicine due to its numerous health benefits, including immune stimulation, anti-ageing, wound healing, and anti-osteoporosis properties. Researchers attribute the therapeutic advantages of DAV to various compounds in its extract, ranging from growth hormones to minerals and amino acids. Recently, there has been renewed interest in these natural products for their potential use in treating chronic diseases such as bone health and development, bacterial infections, and sports supplementation to increase athletic performance. The available literature supports that DAV significantly affects bone development, chondrogenesis, and antimicrobial properties, making it a valuable resource in medical and dental settings. This review aims to provide an in-depth overview of the potential applications of DAV in modern medicine and dentistry.